2 - Development, Social Citizenship and Human Rights: Re-thinking the Political Core of an Emancipatory Project in Africa - Neocosmos, Michael (Africa Development, 2001)
The paper begins from the axiomatic point that, despite the form it eventually took, namely that of a neo-colonial process, development was understood and fought for in Africa as [part of] an emancipatory political project central to the liberatory vision of the pan-African nationalism which emerged victorious at independence. Indeed independence was always seen, by radical nationalism in particular, as only the first step towards freedom and liberation from oppres- sion, the second being economic development. Indeed ‘economism’ and ‘statism’ were mirror images of each other: it was believed that only the economy could liberate humanity and that only the state could drive the economy to progress. Today, the first proposition has been retained but the second has been dropped from hegemonic discourse. Yet the two are inseparable twins; it is in fact the case that just as the latter is false so is the former, for human emancipation is and can only be a political project. While development today is said to be guided by the (not so invisible) “hand of the market”, the state has simultaneously ‘sub- contracted’ many of its development management functions to external bodies such as NGOs. These are frequently simply new parastatals, vehicles for social entrepreneurship for a ‘new’ middle-class of development professionals. We have now a new form of state rule which forms the context for re-thinking de- velopment and politics. Central to this new form of rule is the hegemony of human rights discourse. This paper begins by reviewing the political assump- tions of the nature of citizenship underlying T.H. Marshall’s argument for ‘so- cial rights’; it provides a critique of human rights discourse and civil society from an emancipatory perspective, situating these within the new forms of im- perialism and comments on the character of political parties and social move- ments in understanding political emancipation today. It argues that in Africa, if one is to think an emancipatory project, citizenship must be conceived as active citizenship, and political subjectivity must be thought, not as management or opinions but, following the work of Badiou and Lazarus, as the freedom to think new ‘possibles’.